Rwanda : Social and Economic Background Paper, and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1995)
This paper provides information on the social and economic situation in Rwanda before and after the 1994 civil war. Important social and political developments in the period preceding the war are discussed. The far-reaching consequences of the 1994 civil war, together with the initial reconstruction efforts toward the end of that year, are described. The government's strategy for postwar reconstruction and rehabilitation is outlined, and the various efforts of the international community, including those of the IMF, in supporting Rwanda and the government's strategy are detailed.